1995
DOI: 10.1177/002204269502500409
|View full text |Cite
|
Sign up to set email alerts
|

Drinking Contexts, Alcohol Beliefs, and Patterns of Alcohol Consumption: Evidence for a Comprehensive Model of Problem Drinking

Abstract: The social contexts in which individuals drink and the expected outcomes of that drinking (i.e., individual beliefs about the effects of drinking beverage alcohol) have recently been found to represent conceptually distinct models of alcohol consumption patterns. This paper examines the relationships between contexts, beliefs, and a variety of problem drinking patterns, and reestimates these relationships in a large national probability sample of 2,100 adults (U.S. National Alcohol Survey [National 7], Alcohol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…Researchers have shown that women's peers have an important impact on their drinking behaviors (Demers, 1997;Holyfield, Ducharme, & Martin, 1995;S. C. Wilsnack, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have shown that women's peers have an important impact on their drinking behaviors (Demers, 1997;Holyfield, Ducharme, & Martin, 1995;S. C. Wilsnack, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Research has demonstrated that motivation to drink as a means to cope with negative affect tends to predict more problematic drinking than do enhancement and social drinking motives (Cooper, 1994;Cooper, Russell, Skinner, & Windle, 1992;Holyfield et al, 1995;Kuntsche, Knibbe, Gmel, & Engels, 2005;Rafnsson, Jonsson, & Windle, 2006). Distress tolerance is one factor that is likely to influence coping with negative affect.…”
Section: Distress Tolerance Coping and Alcohol-related Problemsmentioning
confidence: 99%
“…Research indicates solitary drinkers (vs. social drinkers) use alcohol excessively, report more alcohol-related problems, and drink to self-medicate (Christiansen, Vik, & Jarchow, 2002;Holyfield, Ducharme, & Martin, 1995). Solitary drinkers are at higher risk for developing alcohol use disorders compared to those who limit drinking to social events (Abbey, Smith, & Scott, 1993).…”
mentioning
confidence: 99%